2015
DOI: 10.1007/s00244-015-0211-2
|View full text |Cite
|
Sign up to set email alerts
|

Legacy of a Chemical Factory Site: Contaminated Groundwater Impacts Stream Macroinvertebrates

Abstract: 14Legislative and managing entities of EU member states face a comprehensive task since the 15 chemical and ecological impacts of contaminated sites on surface waters need to be assessed. The 16 ecological assessment is further complicated by the low availability, or in some cases, absence of 17 ecotoxicity data for many of the compounds occurring at contaminated sites. We studied the 22show that taxonomical density and diversity of especially sediment dwelling taxa were reduced by 23 > 50% at the sampling si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 53 publications
2
21
1
Order By: Relevance
“…This approach relies on the one‐dimensional analytical solution: q z = κ f s p f c f z l n T Z T L T 0 T L where q z is Darcy flux in the vertical direction (m/s), k fs is the thermal conductivity of the solid‐fluid system (2.2 J/s m K) (Hopmans et al ), p f c f is the volumetric heat capacity of the fluid (4.19 × 10 6 J/m 3 K), z is the depth of measurement (0.4 m), T z is the temperature at depth z (°C) (ranged from 9.8 to 12.2 °C), T L is the temperature of the groundwater which is fixed for all calculations (8.6 °C), and T 0 is the temperature at z = 0 (°C) (ranged from 10 to 12.3°C). This value was measured along with a surface water temperature ( T sw = 18°C) and a bed‐water temperature at depth z ( T z ) at every measurement location (Rasmussen et al ). The T z measurements were made at z = 0.4 m in an effort to reach a zone beneath active horizontal hyporheic flow.…”
Section: Methodsmentioning
confidence: 99%
“…This approach relies on the one‐dimensional analytical solution: q z = κ f s p f c f z l n T Z T L T 0 T L where q z is Darcy flux in the vertical direction (m/s), k fs is the thermal conductivity of the solid‐fluid system (2.2 J/s m K) (Hopmans et al ), p f c f is the volumetric heat capacity of the fluid (4.19 × 10 6 J/m 3 K), z is the depth of measurement (0.4 m), T z is the temperature at depth z (°C) (ranged from 9.8 to 12.2 °C), T L is the temperature of the groundwater which is fixed for all calculations (8.6 °C), and T 0 is the temperature at z = 0 (°C) (ranged from 10 to 12.3°C). This value was measured along with a surface water temperature ( T sw = 18°C) and a bed‐water temperature at depth z ( T z ) at every measurement location (Rasmussen et al ). The T z measurements were made at z = 0.4 m in an effort to reach a zone beneath active horizontal hyporheic flow.…”
Section: Methodsmentioning
confidence: 99%
“…The annual average flow is 2000 L/s and the stream is 8‐ to 12‐m wide and 1‐ to 2.5‐m deep (Balbarini et al ). Groundwater and hyporheic zone water samples collected below the streambed showed that groundwater contaminated by pharmaceutical compounds discharges along a 2‐km stretch of the stream (Rasmussen et al ; Sonne et al ). A discharge area (red rectangle in Figure ) with high groundwater concentrations of benzene, chlorinated ethenes, mainly cis DCE ( cis ‐1,2‐dichloroethene) and vinyl chloride (VC), and pharmaceutical compounds was found (Rønde et al ; Sonne et al ; Balbarini et al ).…”
Section: Study Sitementioning
confidence: 99%
“…The stream has a width of 8 to 12 m and a depth of 1 to 2.5 m. The catchment is dominated by sand and sandy clay and is approximately 200 km 2 . The stream flow ranges from 1500 to 4100 L/s, and the stream is gaining along this specific section (Sonne et al ). A plume of chlorinated ethenes and other contaminants migrates from the former Grindsted factory site, located 1.5 km north of the stream, towards the stream.…”
Section: Study Sitementioning
confidence: 99%
“…Groundwater contamination with chlorinated ethenes has, in recent studies, shown to be a matter of concern for stream water quality (McKnight et al ; Weatherill et al. ; Rasmussen et al ). When groundwater discharges into streams, contaminant plumes appear close to the surface.…”
Section: Introductionmentioning
confidence: 99%